MODERN INTERNET VOCABULARY IN ENGLISH AND RUSSIAN: SIMILARITIES AND BORROWINGS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The rapid growth of digital communication has introduced a wide range of new lexical items into contemporary languages. English, as the global language of technology, has had a particularly strong influence on the development of internet vocabulary in other languages, including Russian. This article explores the similarities, borrowings, and linguistic mechanisms that shape modern English and Russian internet vocabulary. It examines direct loanwords, semantic extensions, phonetic adaptations, hybrid constructions, and the cultural and social factors that contribute to cross-linguistic exchange. The findings show that online discourse encourages linguistic convergence and creativity, resulting in shared digital terminology across both languages.